Safety evaluation of intravenous immunoglobulin in pediatric patients: a retrospective, 1-year observational study. (October 2019) - Elajez, Reem; Ezzeldin, Asmaa; Gaber, Hossamaldein
Background: Intravenous immunoglobulin (IVIG) is a pooled human plasma protein that has shown efficacy in treating a variety of disorders. IVIG is generally well tolerated and has a good safety profile. There are various IVIG products available on the market, which results in differences in efficacy and safety profile. The aim of this study was to assess the safety profile of IVIG use in pediatric patients and its association with other predicted factors. Methods: Retrospective chart review study of all pediatric patients who received IVIG as an inpatient at Hamad General Hospital in Qatar during 2014. The occurrence of adverse drug reactions (ADR) was tested for any association with other predicted factors, such as patient age, IVIG dose, brand, and adherence to infusion protocol. Results: A total of 345 IVIG prescriptions were received by pediatric patients during the study period. Most common documented side effects were: fever (5.8%), chills (2.6%), and headache (2%). Renal insufficiency was observed only in six cases, with five of those in 'Risk' category according to RIFLE criteria. A hypersensitivity reaction was documented in seven patients, despite being premedicated with paracetamol and/or diphenhydramine and following the infusion protocol. None of the predicted factors were found to be significantly associated with ADR incidence except IVIG brand. Conclusions: IVIG generally has a good safety profile in pediatric patients, with low risk of severe ADR. More studies are needed to evaluate the correlation between ADR and IVIG formulation, taking into account other factors that may affect results.